Hubungan Penanganan Komplikasi Kebidanan dan Pelayanan Kesehatan (K4) dengan Kematian Ibu Hamil Hipertensi di Jawa Timur - Fitri Atikasari; Lucia Yovita Hendrati (Universitas Airlangga, 2023)
Background: One of the dangers of midwifery or pregnancy is the mortality of pregnant women with hypertension. By managing midwifery difficulties and health services for pregnant women, efforts may be made to prevent and manage the mortality of pregnant women with hypertension (K4). The management of midwifery difficulties and prenatal care services (K4) reduced in East Java Province in 2021. Objectives: The purpose of this study was to map out the disease's spread and explain how maternal mortality is related to hypertension and its causes. Methods: In 38 East Javan regions and cities, maternal mortality was examined. In order to assess the secondary data from the East Java Health Profile in 2019–2021, this study used the Pearson correlation test. Furthermore, SPSS applications were used to analyze the data. Results: There was a relationship between maternal mortality with hypertension in 2021 and the coverage of midwifery complications (p = 0.000), as well as between the coverage of prenatal care services (K4) and the death of pregnant women with hypertension in 2021 (p = 0.000). Conclusion: The treatment of midwifery problems and the availability of prenatal care services (K4) were factors in the deaths of pregnant women with hypertension. A program of interventional actions that must be carried out while paying more attention to pregnant women's health, particularly for those with hypertension, was required.